2021
DOI: 10.1002/slct.202004536
|View full text |Cite
|
Sign up to set email alerts
|

Acridine‐1,8‐diones: Synthesis and Biological Applications

Abstract: The unpretentious features of acridine‐1,8‐diones viz. presence of N‐heteroatom, electronic behavior, acridine ring skeleton and wide possibilities of diversified substitution, bichromophoric structure and interaction ability with various proteins, make them an interesting scaffold of heterocyclic, medicinal and industrial chemistry. A tremendous development in the field of acridinediones in terms of synthetic strategies, bioactivity, industrial and other applicability has been explored in past four decades. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 205 publications
(272 reference statements)
0
13
0
1
Order By: Relevance
“…На практике результаты, полученные в данной работе, могут найти применение в химических призводствах лазерных красителей [7], медицинских препаратов [8], катализаторов фотополимеризации [9].…”
Section: (а) (б)unclassified
“…На практике результаты, полученные в данной работе, могут найти применение в химических призводствах лазерных красителей [7], медицинских препаратов [8], катализаторов фотополимеризации [9].…”
Section: (а) (б)unclassified
“…Besides, Acetic acid and αmethyl acetic acid derivatives as mentioned in literature possess high potency degree as antiinflammation drugs. [6][7][8][9][10] Literature survey indicated that nitrogen-rich heterocycles such as triazoles, thiadiazoles, and oxadiazoles have attracted attention of many researchers as they have notable biological properties, especially cytotoxic effects. [11][12][13] These molecules of azoles revealed very intensive antmicrobial, antitumor and anticancer activities.…”
Section: Introductionmentioning
confidence: 99%
“…This prominent ring is also suitable for various chemical modifications. Introducing DHP into fused ring systems such as hexahydroquinoline and decahydroacridine has led to the discovery of novel molecules with a vast variety of biological activities [3,4]. DHPs are under investigation not only for medical purposes decahydroacridine has led to the discovery of novel molecules with a vast variety of biological activities [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Introducing DHP into fused ring systems such as hexahydroquinoline and decahydroacridine has led to the discovery of novel molecules with a vast variety of biological activities [3,4]. DHPs are under investigation not only for medical purposes decahydroacridine has led to the discovery of novel molecules with a vast variety of biological activities [3,4]. DHPs are under investigation not only for medical purposes but also for their physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%